Prosthetic valve endocarditis: early and late outcome following medical or surgical treatment. (1st March 2003) - Akowuah, E F; Davies, W; Oliver, S; Stephens, J; Riaz, I; Zadik, P; Cooper, G
Abstract : Objective: To compare the early and late outcome of medical and surgical treatment in patients with prosthetic valve endocarditis within a single unit. Design: All patients with proven prosthetic valve endocarditis treated in one institution between 1989 and 1999 were studied. Results: There were 66 patients (24 female, 42 male), mean (SD) age 57 (14) years. Of these, 28 were treated with antibiotics alone and 38 with a combination of antibiotics and surgery. The in-hospital mortality for the antibiotic group was 46% and for the surgical group, 24%. However, seven patients in the antibiotic group were considered too sick for curative treatment. The mortality in the remaining 21 medically treated patients (6/21; 29%) was not significantly different from that in the surgically treated patients (p = 0.15). Six patients in the medically treated group and one in the surgically treated group required late reoperation. Endocarditis recurred in three patients in the medically treated group, two of whom were treated surgically, and in one patient in the surgically treated group. Kaplan–Meier survival at 10 years was 28% in the medically treated group v 58% in the surgically treated group (p = 0.04). Freedom from endocarditis at five years was 60% in the surgically treated group and 65% in the medically treated group. Conclusions: Prosthetic valve endocarditis is a serious condition with high early and late mortality, irrespective of the treatment employed. These data show that selected patients with prosthetic valve endocarditis can be successfully treated with antibiotics alone. If required, surgery in this difficult group of patients can provide satisfactory freedom from recurrent infection.